(3CfSGH GdCTQGa hCNHGQges - (3CHh GdMSf CMeO Hf jMji Hf LGHQ Hf OGhO, GdHdGPQj,J (B279 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO CKfGA eGOI eG bHd YfhGf (B" (3NHQ Bd GdegdH HbfOGHjd (B" (3, bhdg (B: (3bGdhG (B: (3hdeG hQO MejO Hf YHO Gdedc Hf GdegdH Edjg ai UdH GdCeGf ESJTGQ GdfGS ai CeGfg s
(3BNQgG (B:s
(3BNQ GdehLhO HYfhGf (B" (3HhG YHO GdOGQ Hf bUi (B" (3, bhdg (B: (3hefge TjHI Hf YKeGf GdCbUi Hf CHj WdMI , hTjHI GdMGLH HYO YKeGf Hf WdMI hcGf TjHI gPG TOjOkG Ydi GdeSdejf , hcGf eef ONd GdCeGf jhe GdaJM , aJM ecI , adeG cGf jhe Mfjf s
(3ef GdfSNI GdChdi faSgGs
(3hfXf Cf gPG GdLRA djS ef GdfSNI faSgG dGNJdGa GdNW hJQbje GdUaMGJs
(3gPg GdfSNI UhQJ Yf OGQ GdcJH GdeUQjI JMJ Qbe (B1103 (3JGQjN hgj Yf fSNI YGTQ GafOi HESJGfHhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B267s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B147 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B216 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B179s
Keywords: (3GdJGQjNs